Prevalence of BRCA1 and BRCA2 mutations in unselected breast cancer patients from Colombia (2012)
ABSTRACT: Background: Approximately 5% of all breast cancers can be attributed to a mutation in the BR- CA1 and BRCA2 genes. The genetic component of breast cancer in Colombia has been, for the most part, studied only on cases from the Bogota region. In fact, five founder mutations have been identified in two previous studies of breast cancer patients in the Bogota region. It is important that the frequency of mutations be established among unselected cases of breast cancer of other regions of Colombia in order to estimate the true genetic burden of this cancer in Colombia and to plan genetic and preventive services accordingly. The aim of this study was to establish the mutation frequencies of the BRCA genes in breast cancer patients unselected for family history from Medellin, Colombia. Methods: We enrolled 283 unselected women with breast cancer from a large public hospital in Medellin, Colombia. A detailed family history was obtained from each patient and a blood sample was processed for DNA analysis. Mutations in BRCA1 and BRCA2 were sought using a combination of techniques including a Hispanic BRCA mutation testing panel. All mutations were confirmed by direct sequencing. Results: Genetic testing was successfully completed on 248 of the 283 cases (88%). Among these 248 cases, three deleterious mutations were identified (two in BRCA1 and one in BRCA2) representing 1.2% of the total. The average age of breast cancer in the mutation-positive cases was 34 years. The two BRCA1 mutations were founder mutations (3450delCAAG in exon 11 and A1708E in exon 18). The BRCA2 mutation was in exon 11 (5844delAGTAA) and has never been reported in individuals of Colombian descent. Among the three mutation-positive families there was one breast cancer family and two families with no history of cancer. We also identified four variants of unknown significance (one in BRCA1 and three in BRCA2). Conclusion: Approximately 1.2% of all breast cancer cases in the Medellin region of Colombia are attributable to a BRCA1 or BRCA2 mutation.